Distribución geoespacial y factores asociados a la mortalidad fetal del Hospital Regional de Loreto 2018-2022 - Noriega Trigoso, Lidia Patricia (2023)
Objectives. Determine the geospatial distribution and factors associated with fetal death registered at the Loreto Regional Hospital from 2018 to 2022. Materials and methods. Observational, descriptive and cross-sectional study. The clinical history databases of fetal deaths registered at the Loreto Regional Hospital between the years 2018 to 2022 were used. Data on maternal, neonatal characteristics, the temporal profile of the registry, as well as its spatial or geographic registration were assessed. The data selected from the search strategy were exported and descriptive statistics of frequency and percentage were obtained. QGIS software was used to generate geographic and heat maps for population density by cluster and by specific points. Results. Of 246 registered cases, 03 were excluded, leaving a sample of 243 cases of fetal deaths during the study period, where it was found that the year 2019 had the highest number of fetal deaths registered with 33.9% of the total in the period studied, in contrast 2020 had a decrease in the number of fetal deaths registered, representing 16.4% of the total. The districts with the highest density of cases were San Juan, Iquitos and Punchana, and the provinces with the most intense hot spots were Maynas, Loreto and Ramón Castilla. A significant association was observed between area of residence and fetal death (p=0.001), with a higher incidence in the urban area compared to the rural area. In addition, a significant relationship was detected between educational level and fetal death (p=0.020), with a higher percentage of fetal deaths among mothers with primary education in the non-capital district. Conclusions. Fetal deaths registered at the Loreto Regional Hospital are distributed predominantly towards the east and south of the region, with higher rates in the provinces of Maynas, Loreto and Ramón Castilla. Maternal education and area of origin are factors that are associated with fetal mortality in districts with higher population density of Loreto.